2019
DOI: 10.3389/fphar.2018.01553
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II-Regulated Autophagy Is Required for Vascular Smooth Muscle Cell Hypertrophy

Abstract: Hypertension is a disease associated to increased plasma levels of angiotensin II (Ang II). Ang II can regulate proliferation, migration, ROS production and hypertrophy of vascular smooth muscle cells (VSMCs). However, the mechanisms by which Ang II can affect VSMCs remain to be fully elucidated. In this context, autophagy, a process involved in self-digestion of proteins and organelles, has been described to regulate vascular remodeling. Therefore, we sought to investigate if Ang II regulates VSMC hypertrophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 60 publications
(88 reference statements)
5
23
1
3
Order By: Relevance
“…It has been reported that TLR4-induced ATG7/autophagy inhibits enterocyte migration via induction of RhoA-mediated actin stress fibers 59 . Another study by Mondaca-Ruff et al 60 showed that angiotensin II induces autophagy via the RhoA/ ROCK pathway to cause vascular smooth muscle cells (VSMC) hypertrophy. Thus, ATG7/autophagy can act both upstream and downstream of RhoA/ROCK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that TLR4-induced ATG7/autophagy inhibits enterocyte migration via induction of RhoA-mediated actin stress fibers 59 . Another study by Mondaca-Ruff et al 60 showed that angiotensin II induces autophagy via the RhoA/ ROCK pathway to cause vascular smooth muscle cells (VSMC) hypertrophy. Thus, ATG7/autophagy can act both upstream and downstream of RhoA/ROCK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…As a major component of the vessel wall, VSMCs are responsible for the control of blood ow and arterial pressure by regulating the lumen's diameter of resistance vessels in response to Ang-II [20]. Ang-II induced autophagy by increasing Beclin-1, Vps34, Atg-12-Atg5, Atg4 and Atg7 protein levels, Beclin-1 phosphorylation, and the number of autophagic vesicles [21]. Here, we found that Atg7 was up-regulated in Ang-II treated VSMCs, as our previous study showed that metformin represses the pathophysiology of AAA by inhibiting autophagy pathway [15], in this study, we showed that the induced expression of Atg7 in AAA was reversed by metformin.…”
Section: Discussionmentioning
confidence: 99%
“…Later, LC3 I forms a conjugate with phosphatidylethanolamine (PE) by the transforming action of ATG7 and ATG3, thereby generating LC3 II. LC3 II then attaches to the autophagosome membrane triggering its elongation ( Mondaca-Ruff et al, 2018 ). The lysosomal proteolytic enzyme Cathepsin D is the only aspartic-type protease that is ubiquitously found in every cell of the human body.…”
Section: Introductionmentioning
confidence: 99%